An Overview on Antifungal Resistance - Nashat Shahin, Marwa; Anwer Refky, Mohamed; Saad Eldeen, Sahar Mohamed; M. Negm, Essamedin; Gouda Moayed, Haitham; Hassan Naser, Eslam Ahmed (Cuestiones de Fisioterapia, 2024)
Fungal infections account for substantial morbidity and mortality worldwide, especially in immunocompromised populations. While antifungal agents such as azoles, echinocandins, and amphotericin B have improved outcomes, increasing resistance among clinically important species poses major therapeutic challenges. Unlike antibacterial resistance, antifungal resistance develops more slowly but is particularly concerning due to the limited number of antifungal drug classes available. Resistance mechanisms include mutations in drug targets, efflux pump overexpression, biofilm formation, and environmental exposure to antifungal agents, particularly in agriculture. The global rise of resistant pathogens highlights the urgent need for enhanced diagnostics, surveillance, and stewardship strategies.